2020
DOI: 10.1029/2019ms001812
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Earth System Model RegCM‐ES: Evaluation of the Mediterranean Climate and Marine Biogeochemistry

Abstract: We introduce a new version of the Earth System Regional Climate model RegCM‐ES and evaluate its performances for the first time over the Mediterranean region. The novel aspect of this coupled system is the possibility to simulate the dynamics of the marine ecosystem through a biogeochemical model, BFM (Biogeochemical Flux Model), coupled online with the ocean circulation model MITgcm (MIT general circulation model). The validation of atmosphere and ocean components has shown that the model is able to capture i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 122 publications
(349 reference statements)
3
11
0
Order By: Relevance
“…In the case of NO 3 , intense signals are located in the Gulf of Lions, Adriatic Sea, Aegean Sea and Rhodes Gyre. The NO 3 input from rivers in the Northern Adriatic (associated with the Po River inflow) and Aegean Sea (associated with the inflow at the Dardanelles Strait) is particularly remarkable, and is in good agreement with ded- icated regional studies (Solidoro et al 2009, Souvermezoglou et al 2014, Richon et al 2018b, Di Biagio et al 2019, Reale et al 2020).…”
Section: Methodssupporting
confidence: 76%
See 3 more Smart Citations
“…In the case of NO 3 , intense signals are located in the Gulf of Lions, Adriatic Sea, Aegean Sea and Rhodes Gyre. The NO 3 input from rivers in the Northern Adriatic (associated with the Po River inflow) and Aegean Sea (associated with the inflow at the Dardanelles Strait) is particularly remarkable, and is in good agreement with ded- icated regional studies (Solidoro et al 2009, Souvermezoglou et al 2014, Richon et al 2018b, Di Biagio et al 2019, Reale et al 2020).…”
Section: Methodssupporting
confidence: 76%
“…Crise et al 1999, Manca et al 2004, Richon et al 2018a,b, 2019, Di Biagio et al 2019, Reale et al 2020. Relative high values of PO 4 are found in the Alboran Sea and Gulf of Lions (Crise et al 1999, Manca et al 2004, Richon et al 2018a,b, Di Biagio et al 2019, Reale et al 2020, while relatively low PO 4 val-ues are found in the Southern Adriatic, Northern Ionian, Aegean Sea and the Rhodes Gyre. In the case of NO 3 , intense signals are located in the Gulf of Lions, Adriatic Sea, Aegean Sea and Rhodes Gyre.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Nutrient patterns in the Alboran Sea have been associated with the distinct vertical mixing that supplies the surface layer with nutrients (Lazzari et al, 2012;Reale et al, 2020).…”
Section: Surface Layermentioning
confidence: 99%